2022
DOI: 10.1002/msc.1710
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for atlantoaxial dislocation in rheumatoid arthritis: A comparative study

Abstract: Background The objective of the study was to assess clinical and imaging features of rheumatoid arthritis associated with atlantoaxial dislocation (RA‐AAD) in comparison to RA without AAD (RA‐C) and to identify the associated factors to AAD. Methods This was a retrospective comparative study including RA patients over 18 years old. The control group of RA‐C was matched according to age (±2 years), gender, and RA duration (±2 years). General data, RA characteristics, AAD features, and treatment modalities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…In fact, overlapping anatomical structures and RA joint destruction make the diagnosis of this form challenging on standard radiographs (Ball & Sharp, 1971; Kotecki et al., 2021). In agreement with data from previous studies, we found that 7.8% of G1 patients had combined AAS (Ben Tekaya et al., 2022; Bénazet et al., 1996; Teinturier et al., 1982; Younes et al., 2009). The Table 3 illustrates the distribution of patients with RA according to the form of AAS in our study and in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, overlapping anatomical structures and RA joint destruction make the diagnosis of this form challenging on standard radiographs (Ball & Sharp, 1971; Kotecki et al., 2021). In agreement with data from previous studies, we found that 7.8% of G1 patients had combined AAS (Ben Tekaya et al., 2022; Bénazet et al., 1996; Teinturier et al., 1982; Younes et al., 2009). The Table 3 illustrates the distribution of patients with RA according to the form of AAS in our study and in the literature.…”
Section: Discussionsupporting
confidence: 93%